Environmental Sustainability in France: The Role of Alternative and Nuclear Energy, Natural Resources, and Government Spending - Ridwan, Mohammad; Raihan, Asif; Ahmad, Shakil; Karmakar, Sourav; Paul, Pramila (Journal of Environmental and Energy Economics, 2023)
The worldwide community is worried due to various ecological modifications. The change of climate, desertification, logging, coastal erosion, overfishing, loss of biodiversity, and soil resource depletion are all causes that contribute to ecological harm. Quite a few observers have pointed out that these problems add up to substantial alterations to Earth's surface brought about by human activity. Using the framework of the environmental Kuznets curve (EKC), this investigation analyzes the influences of alternative energy resources and natural resources alongside government spending on France's ecological sustainability throughout 1990-2021. Long-run estimates are calculated with completely modified least squares (FMOLS), and the empirical analysis's robustness is examined with dynamic ordinary least squares (DOLS). Long-term estimations show an opposing association concerning carbon dioxide (CO2) emissions with renewable and nuclear energies, natural resources, and government spending, whereas a positive liaison between CO2 emissions with economic development. However, CO2 emissions have a negative association with the square of economic progression, lending credence to EKC. As the economy grows, environmental sustainability declines. In the long run, EKC will help the environment progress for the better. Implications for policy, research gaps, and future directions are discussed to round out the study.